2016
DOI: 10.2134/jeq2016.01.0004
|View full text |Cite
|
Sign up to set email alerts
|

The Extent of Manure Removal from Storages and Its Impact on Gaseous Emissions

Abstract: Manure remaining in storage due to incomplete removal is a source of microbial inoculum that may affect methane (CH), nitrous oxide (NO), and ammonia (NH) emissions during subsequent storage. Manure removal was studied by loading fresh manure into outdoor concrete tanks (10.6 m) that contained previously stored manure (inoculum) at six levels (0, 5, 10, 15, 20, and 25%, with 0% representing an empty tank). Emissions were continuously measured for 6-mo storage periods (warm and cold seasons) using flow-through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 14 publications
1
23
1
Order By: Relevance
“…The cumulative NH 3 emissions for the 160 d of monitoring were 641, 376, and 304 g m −2 for the control, medium pH, and low pH tanks, respectively (Table 2). Our results are similar to Ngwabie et al (2016), who reported on average NH 3 emissions of 450 g m −2 from stored liquid dairy manure (182 d) with 0 to 25% inoculum.…”
Section: Resultssupporting
confidence: 92%
“…The cumulative NH 3 emissions for the 160 d of monitoring were 641, 376, and 304 g m −2 for the control, medium pH, and low pH tanks, respectively (Table 2). Our results are similar to Ngwabie et al (2016), who reported on average NH 3 emissions of 450 g m −2 from stored liquid dairy manure (182 d) with 0 to 25% inoculum.…”
Section: Resultssupporting
confidence: 92%
“…() and Ngwabie et al. () found cumulative N 2 O emissions typically exceeding 20 g m −2 . The observed NH 3 emission pattern and low N 2 O emissions are consistent with the lack of crust formation on the tank surface, which favors NH 3 emission over N 2 O emission (Aguerre, Wattiaux, & Powell, ; Hansen et al., ; Wood, Gordon, Wagner‐Riddle, Dunfield, & Madani, ).…”
Section: Resultsmentioning
confidence: 93%
“…Ngwabie et al. () conducted a spring‐removal inoculum study using the same experimental site and setup as the current study. Although the source of the manure was different, this prior trial provided a useful means of comparison for seasonal inoculum removal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations